AESTHETICS AND VISUAL CONNOTATIONS OF RAJASTHANI FOLK ARTS: A CRITICAL STUDY - Nath, Pinak Pani; Shanti (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In Indian culture folk arts like Aipan Art, Miniature Painting, Bhil Art, Dokra Art, Godna Art, Kalamkari Painting, Kalighat Painting, Kavad Art, Mural Painting, Madhubani Art, Mandala Art, Mandana Painting, Pattachitra, Phad Painting, Pichwai Painting, Sanjhi Art, Warli Painting and many more are passed down from one generation to another without changing its cultural and traditional vibrancy, that is why Indian folk arts are still alive and these are successfully taught informally. Indian folk arts are not just expressions of artists, but a way to portray their stories, memories, values, and beliefs. The folk arts are ethnic, simple, vibrant, and colourful in nature. Folk art plays an important role for the richness of Indian art and culture. The folk arts show the history and the heritage of India. In Indian art, culture and tradition, Rajasthan stands as the most colourful and breath-taking state with its various art forms and unique culture. Reflection of uniqueness can be seen in Mandana, Pichwai and Kavad. These traditional art forms depicting various gods, goddess, and folk tales. These folk arts are affected by many critical situations in time to time, but these folk arts are continuously maintaining their tradition vibrancy.